LGBTQIA+: tips for inclusion and safety - RHiME, Editor (Research and Humanities in Medical Education, 2019)
Want to live in an LGBTQIA+ affirming world? Here are the links to important ways in which we can support each other and create a safe, inclusive world: An Ultimate Guide To Online Safety for the LGBTQ Community Most LGBTQ are Cyberbullied. Here’s How to Stay Safe Online The SMB Guide to Success in the LGBTQ Market (2019 Research) LGBTQ cyberbullying: A guide for parents and educators